Electrospun porous poly(tetrafluoroethylene-co-hexafluoropropylene-co-vinylidene fluoride) membranes for membrane distillation. Issue 89 (13th December 2017) - Zhang, Yong; Yang, Bin; Li, Kuiling; Hou, Deyin; Zhao, Changwei; Wang, Jun
Abstract : Novel THV electrospun membrane exhibits enhanced membrane distillation performance. Abstract : A novel terpolymer (abbreviated as THV), which is a copolymer of tetrafluoroethylene, hexafluoropropylene, and vinylidene fluoride, that possesses advantages of excellent hydrophobicity, mechanical properties, and chemical resistance is an ideal material for membrane distillation. In this study, THV hydrophobic membranes were fabricated by the electrospinning method. Morphology and properties (pore size distribution, liquid entry pressure, porosity, and contact angle) of the THV electrospun membranes with various fabrication conditions (solvent composition, THV concentration, and applied voltage) were systematically studied. Under the optimized condition, the membrane exhibited a good structure, wetting resistance, and surface hydrophobicity. The mean pore size, liquid entry pressure of water (LEPw ), and contact angle were 0.79 μm, 118.0 kPa, and 130.7°, respectively. Owing to the advantages of the raw material and fabrication method, the membrane showed excellent mechanical properties and desalination performance. The tensile strength was 5.41 MPa, and the elongation at break was 247.9%, which were 2.47 and 5.61 times higher than those of the poly(vinylidene fluoride) (PVDF) membrane, respectively. Additionally, the membrane distillation flux was 4.42 kg m −2 h −1, which was 1.93 times higher than that of the PVDF counterpart obtained under the same test condition via sweeping gas membrane distillation, and the salt rejection rate was higher than 99.8%.